Fabrication and application of superhydrophilic surfaces: a review - Zhang, Liang; Zhao, Ning; Xu, Jian (Journal of adhesion science and technology, 2014)
Extreme wetting behaviors have been the subject of numerous studies in recent decades. Superhydrophilic surfaces with water contact angle lower than 5° is one of the most exciting research areas which has attract much attention. The ultrafast drying of such surfaces can provide outstanding properties such as antifogging, evaporative cooling, self-cleaning, and others. We review here the basic strategies and recent progress in fabricating superhydrophilic surfaces. And smart surfaces combining superhydrophilic and superhydrophobic abilities are highlighted, including surfaces with stimuli reversible wettability, patterning wettability, and gradient wetting. We also provide insights into the applications of the highly wettable surfaces, especially in devising new potentials.